Distribuição do mercúrio nas águas superficiais do Rio Madeira - Ayres, Gisele Antunes (2004)
The present work was accomplished in Rio Madeira among the city of Porto Velho (RO) and Rio Amazonas (AM), located in the Amazon basin. The results presented in this work were obtained in two trips during the period of 1997, accomplished by Lacerda and collaborators, and 2002 by UFF/UNIR, with the orientation of GPS the samples of superficial waters were collected in the same points established in 1997 (Lechler et al., 2000), with the objective of evaluating the variation in the mercury concentrations, to determine and to compare the partition among the periods of 1997 and 2002. in order to verify the effect of the decrease of the claim of gold and of the changes in the uses of the earth in the transport of the mercury along Rio Madeira, using the technique of generation of cold vapor with pré-concentration in gold coupled in an apparel of espectrofotometria of atomic fluorescência TEKRAN 2500, presenting a detection limit around 0,1ng/L for determination of dissolved Hg and 0,6ng/L for total Hg and Hg associated to the material particulado in suspension. The concentrations of dissolved Hg varied of 0,44 0,83ng/L and 0,30 to 1,14ng/L, and for total Hg of 3,03 at 49,5ng/L and 3,00 to 59,6 ng/L and for Hg in TSS went from 68 to 251ng/g and 9,6 to 122,1 ng/g among the periods of 1997 and 2002 respectively. The concentrations of dissolved Hg didn't vary significantly and they meet inside of the strip reportada for another rivers of Amazônia. However, they happened significant modifications in the distribution of Hg associated to the material particulado in suspension. In 1997, the concentrations of Hg, in mass, associated TSS were significantly larger than in 2002. The results suggest that happened an alteration in the distribution of Hg in Rio Madeira waters.